Heparan sulfates and heparan sulfate binding proteins in sepsis - Liao, Yi-En; Liu, Jian; Arnold, Katelyn (Frontiers in Molecular Biosciences, 2023)
Heparan sulfates (HSs) are the main components in the glycocalyx which covers endothelial cells and modulates vascular homeostasis through interactions with multiple HS binding proteins (HSBPs). During sepsis, heparanase increases and induces HS shedding. The process causes glycocalyx degradation, exacerbating inflammation and coagulation in sepsis. The circulating HS fragments may serve as a host defense system by neutralizing dysregulated HSBPs or pro-inflammatory molecules in certain circumstances. Understanding HS and HSBPs in health and sepsis is critical to decipher the dysregulated host response in sepsis and advance drug development. In this review, we will overview the current understanding of HS in glycocalyx under septic condition and the dysfunctional HSBPs as potential drug targets, particularly, high mobility group box 1 (HMGB1) and histones. Moreover, several drug candidates based on HS or related to HS, such as heparanase inhibitors or heparin binding proteins (HBPs), will be discussed regarding their recent advances. By applying chemical or chemoenzymatic approaches, the structure-function relationship between HS and HSBPs is recently revealed with structurally defined HS. Such homogenous HS may further facilitate the investigation of the role of HS in sepsis and the development of carbohydrate-based therapy.